A review on relationship of SNP at rs2228570 of VDR gene and different diseases in different populations - Khan, Md. Sazzad (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2023.